Socio-economic consequences of military conflicts in the Donetsk region and priority areas of the regional renewal - Yefremenko, V.; Gavrysh, O. (Економічний вісник Донбасу, 2017)
The socio-economic consequences of military conflicts in the Donetsk region by types of economic activity are analyzed, the state of damaged and restored objects of the infrastructure of Donetsk region as a result of military actions is analyzed, problems of socio-economic development of the Donetsk region are determined, sources for the renewal of social and economic life on the territory of the Donetsk region are analyzed and proposals for the restoration of the Donetsk region territory are developed. Оцінено соціально-економічні наслідки воєнних дій в Донецькій області за видами економічної діяльності, проаналізовано стан пошкоджених та відновлених об’єктів інфраструктури Донецької області внаслідок воєнних дій, визначено проблеми соціально-економічного розвитку Донецької області, проаналізовано джерела для відновлення соціального та економічного життя на території Донецької області та розроблено пропозиції по відновленню території Донецької області. Дана оценка социально-экономических последствий военных действий в Донецкой области по видам экономической деятельности, проанализировано состояние поврежденных и восстановленных объектов инфраструктуры Донецкой области в результате военных действий, определены проблемы социально-экономического развития Донецкой области, проанализированы источники для восстановления социальной и экономической жизни на территории Донецкой области и разработаны предложения по восстановлению территории Донецкой области.